Evaluation of an Acne Severity Grading Self-Assessment System Suitable for the Thai Population – A Pilot Study - Pakornphadungsit K; Harnchoowong S; Wattanakrai P (Dove Medical Press, 2023)
Kallapan Pakornphadungsit, Sarawin Harnchoowong, Penpun Wattanakrai Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Penpun Wattanakrai, Division of Dermatology, Department of Internal Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 ext 4, Email maypenpun@gmail.comBackground: Patient self-assessment is a potential tool in clinical practice to obtain subjective information of acne severity also in clinical trials to assess the general population in research and epidemiologic studies. The patient self-evaluation of acne severity has not yet been developed in Thailand.Objective: We aimed to validate an acne severity grading self-assessment suitable for the Thai population.Methods: A pilot study was conducted in 77 volunteers with acne lesions. We developed the Thai Global Evaluation Acne Scale (TGEA) and Thai Global Acne Grading System (TGAGS) by translating and adapting the original version. Patient self-assessment of acne severity was performed in two rounds. A training session about acne was provided to all participants lesions before starting the second round. Reliability between the self-assessment and clinician assessment of acne severity was statistically assessed.Results: For TGEA, 48.05% participants rated their acne severity corresponded with the clinicians (Cohen's kappa coefficient, kappa = 0.26). After receiving the training, 79.22% subjects responded their acne severity corresponded with the clinicians (kappa = 0.66). For TGAGS, 77.92% patients who answered their acne severity corresponded with the clinicians (kappa = 0.52). After receiving the training, 94.80% participants responded their acne severity corresponded with the clinicians (kappa = 0.89). For raw score of the TGAGS, the intraclass correlation coefficient (ICC) during the self-assessment of acne severity compared to the clinician assessments was 0.54 and it increased to 0.79 after the training.Conclusion: Due to the almost perfect reliability, we suggested that TGAGS is a reliable subjective self-assessment of acne severity suitable for the Thai population. The training is essential in enhancing the reliability of this instrument. Our study's findings can facilitate clinical practice and research studies.Keywords: subjective self-assessment, acne severity, training